Epigenetic and non-epigenetic mode of SIRT1 action during oocyte meiosis progression - Nevoral, Jan; Landsmann, Lukas; Stiavnicka, Miriam; Hosek, Petr; Moravec, Jiri; Prokesova, Sarka; Rimnacova, Hedvika; Koutna, Eliska; Klein, Pavel; Hoskova, Kristyna; Zalmanova, Tereza; Fenclova, Tereza; et al. (Journal of animal science and biotechnology, 2019)
BACKGROUND: SIRT1 histone deacetylase acts on many epigenetic and non-epigenetic targets. It is thought that SIRT1 is involved in oocyte maturation; therefore, the importance of the ooplasmic SIRT1 pool for the further fate of mature oocytes has been strongly suggested. We hypothesised that SIRT1 plays the role of a signalling molecule in mature oocytes through selected epigenetic and non-epigenetic regulation. RESULTS: We observed SIRT1 re-localisation in mature oocytes and its association with spindle microtubules. In mature oocytes, SIRT1 distribution shows a spindle-like pattern, and spindle-specific SIRT1 action decreases α-tubulin acetylation. Based on the observation of the histone code in immature and mature oocytes, we suggest that SIRT1 is mostly predestined for an epigenetic mode of action in the germinal vesicles (GVs) of immature oocytes. Accordingly, BML-278-driven trimethylation of lysine K9 in histone H3 in mature oocytes is considered to be a result of GV epigenetic transformation. CONCLUSIONS: Taken together, our observations point out the dual spatiotemporal SIRT1 action in oocytes, which can be readily switched from the epigenetic to non-epigenetic mode of action depending on the progress of meiosis.
Keywords: SIRT1; Sirtuin 1; In vitro maturation; Epigenetics; Oocyte; Histone code